(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The review presents materials reflecting the functional formation of the digestive organs, that is, the “maturation” of their enzymatic activity. It has been established that the alimentary factor plays the main role in the “ripening” of the digestive system. Cases of maternal pathology adversely affect the development of the digestive system